Ecofeministic Solicitude in the Poem the Trees and the Tree Agreement – A Comparative Study - Dr. N. Jennifer Cynthia, (International Journal of Scientific Research in Science and Technology, 2024)
It is in nature where we truly connect with the mother and ourselves. Be eco-friendly, save the environment. Ecofeminism is a political and intellectual movement that combines feminism and environmentalism. It argues that the oppression of women and the degradation of the environment are linked, and that gender equality can be key to environmental sustainability. The aim of ecofeminism is equality in society and eliminating patriarchy. This paper throws light on the significance of trees and how they symbolize the growth of female empowerment and patriarchal notions. In both poems, trees are described as females who are ready to renew the forest. The two poets in their poems portray how trees face ups and downs in their lives, just like humans. This research paper critically analyses poems of the prolific American writers Adrienne Rich and Elise Paschen who always shed light on women’s issues, conservation of nature and also address issues on deforestation. The paper aims to study their writings through the lenses of Ecofeminism that explores the parallels between the constraints experienced by both women and nature.
Keywords: Ecofeminism; environmentalism; patriarchy; women; nature; trees; deforestation